Epidemiological trends and pathogen analysis of pediatric acute respiratory infections in Hanzhong Hospital, China: insights from 2023 to 2024 - He, Yuanfang; He, Xiaoliang; He, Ning; Wang, Peipei; Gao, You; Sheng, Jiexin; Tang, Jin (Frontiers in Public Health, 2025)
BackgroundAcute respiratory infections (ARIs) are a leading cause of morbidity in children. Understanding the distribution of respiratory pathogens is crucial for effective prevention and treatment. This study analyzed the prevalence and epidemiological characteristics of ARIs in children from 2023 to 2024.MethodologyThis study included 9,294 children aged 0–18 years with ARI symptoms who were treated between July 2023 and August 2024. Respiratory samples were tested using polymerase chain reaction (PCR) for eight common viruses. Data were analyzed by age and gender to assess pathogen distribution and demographic patterns.ResultsA total of 14,722 samples were enrolled, with 2,888 (19.62%) testing positive for at least one pathogen. Among these, single-pathogen infections were predominant (97.66%, 2,756/2,822), while co-infections were less frequent (2.34%, 66/2,822). The three most common pathogens were adenovirus (ADV, 33.24%), Mycoplasma pneumoniae (MP, 25.07%), and whooping cough (WC, 22.78%). No significant gender differences were observed in the overall positive rate or pathogen distribution (p > 0.05). Pathogen detection rates varied significantly by age group (χ2 = 110.03, p < 0.001), with WC and MP being most prevalent in school-age children (χ2 = 104.58, p < 0.001; χ2 = 11.546, p = 0.009, respectively) and Flu A more frequent in preschool children (χ2 = 38.738, p < 0.001). MP, WC, ADV, human rhinovirus, and human metapneumovirus were detected throughout the year.DiscussionThe findings highlight that ARIs in children are primarily caused by single respiratory pathogens, with significant age-related differences in pathogen prevalence. These results emphasize the need for age-specific prevention strategies, such as targeted vaccination programs and public health interventions, particularly for school-age children during peak transmission periods.